Indocyanine Green Fluorescence Using in Conduit Reconstruction for Patients With Esophageal Cancer to Improve Short-Term Clinical Outcome: A Meta-Analysis - Hong, Zhi-Nuan; Huang, Liqin; Zhang, Weiguang; Kang, Mingqiang (Frontiers in Oncology, 2022)
Objectives This meta-analysis evaluated the short-term safety and efficacy of indocyanine green (ICG) fluorescence in gastric reconstruction to determine a suitable anastomotic position during esophagectomy. Methods The Preferred Reporting Items for Systematic Reviews and Meta-Analyzes 2020 (PRISMA) were followed for this analysis. Results A total of 9 publications including 1,162 patients were included. The operation time and intraoperative blood loss were comparable in the ICG and control groups. There was also no significant difference in overall postoperative mortality, reoperation, arrhythmia, vocal cord paralysis, pneumonia, and surgical wound infection. The ICG group had a 2.66-day reduction in postoperative stay. The overall anastomotic leak (AL) was 17.6% (n = 131) in the control group and 4.5% (n = 19) in the ICG group with a relative risk (RR) of 0.29 (95% CI 0.18–0.47). A subgroup analysis showed that the application of ICG in cervical anastomosis significantly reduced the incidence of AL (RR of 0.31, 95% CI 0.18–0.52), but for intrathoracic anastomosis, the RR 0.35 was not significant (95% CI 0.09–1.43). Compared to an RR of 0.35 in publications with a sample size of <50, a sample size of >50 had a lower RR of 0.24 (95% CI 0.12–0.48). Regarding intervention time of ICG, the application of ICG both before and after gastric construction had a better RR of 0.25 (95% CI 0.07–0.89). Conclusions The application of ICG fluorescence could effectively reduce the incidence of AL and shorten the postoperative hospital stay for patients undergoing cervical anastomosis but was not effective for patients undergoing intrathoracic anastomosis. The application of ICG fluorescence before and after gastric management can better prevent AL. Systematic Review Registration PROSPERO, CRD:42021244819.